Modelación analítica de accesorios tipo curva para el flujo en tuberías a presión - Martínez Delgado, Ivanna Maleny (2023)
The installation and operation of potable water piping networks can face various obstacles that vary in magnitude, due to the diversity of elements required for its operation. In the Ecuadorian context, several types of curved fittings are available, each with its own design, which have been extensively tested. In this study, the Hidrotubos and Tigre brands, which are recognized in the Ecuadorian market, were specifically evaluated. A prototype was developed to obtain data related to pressures and flow rates. These data were entered into relevant equations, resulting in the loss coefficients in the accessories and energy loss. These results were then compared to standards previously established in reference manuals. Overall, this work provides a detailed assessment of the challenges associated with the installation and operation of drinking water networks, highlighting the importance of proper selection of fittings and validation of their performance through empirical methods and accurate calculations.